210Po concentration in selected calanoid copepods in the northern Arabian Gulf. (August 2018) - Uddin, Saif; Behbehani, Montaha; Al-Ghadban, Abdulnabi; Sajid, Sufiya; Al-Zekri, W.; Ali, Mohammad; Al-Jutaili, Sarah; Al-Musallam, Lamya; Vinod, Vanitha; Al-Murad, Mohammad; Alam, Faiz
Abstract: Copepods are the most abundant metazoans, forming a vital food chain link between the primary producers the phytoplankton and fish. This study presents baseline information on the concentration of 210 Po among calanoid copepods isolated from the Kuwait marine area. The concentration of 210 Po in six species of copepod, including Subeucalanus flemingeri, Parvocalanus crassirostis, Acartia pacifica, Calanopia elliptica, Acrocalanus gibber, and Euterpina acutifrons were 151.3–158.8 Bq kg −1 wwt, 121.1–129.5 Bq kg −1 wwt, 51.23–54.91 Bq kg −1 wwt, 38.88–40.09 Bq kg −1 wwt, 38.07–38.29 Bq kg −1 wwt, and 33.46–36.50 Bq kg −1 wwt, respectively. The 210 Po concentration in seawater shows a seasonal variation, with a higher concentration range of 0.58–0.70 mBq L −1 during summer and autumn, while a lower concentration is found (0.30–0.38 mBq L −1 ) during winter and spring. The concentration factor among the copepods varies between 8 ∗ 10 4 and 5 ∗ 10 5 that is an order of magnitude higher than the diatoms and dinoflagellates. Highlights: This is the first baseline for 210 Po in calanoid copepods from northern Gulf. 210 Po concentration in copepods is an order of magnitude higher than in phytoplankton. The concentration factor varies between 0.8 and 5.3 ∗ 10 5 . The study provides a more realistic basis for reference CF value for copepods.